2021
DOI: 10.1159/000512889
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Non-Response to Vismodegib in Locally Advanced Basal-Cell Carcinoma

Abstract: <b><i>Background:</i></b> Vismodegib has shown clinical efficacy in the management of locally advanced basal cell carcinomas (laBCC). However, non-response to vismodegib is observed in 2–13.5% of patients in clinical studies. The purpose of this study was to identify factors associated with non-response to vismodegib in patients with laBCC. <b><i>Methods:</i></b> We carried out a retrospective multicenter study, including patients with laBCC treated with vismodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Intermittent dosing was indeed recently reported as a cause favouring non-response to vismodegib. 9 In line with previous reports, we observed a median time to best response of 5.0 months and to CR of 4.9 months. 3,10 In our series, patients with toxicities more frequently achieved NCR to vismodegib.…”
supporting
confidence: 92%
“…Intermittent dosing was indeed recently reported as a cause favouring non-response to vismodegib. 9 In line with previous reports, we observed a median time to best response of 5.0 months and to CR of 4.9 months. 3,10 In our series, patients with toxicities more frequently achieved NCR to vismodegib.…”
supporting
confidence: 92%
“…Patients experiencing multiple AEs might undergo dose reduction or treatment discontinuation, which may affect tumor response outcomes. To this regard, some authors reported an association between intermittent dosing and nonresponse to HHI [18,20], while others claimed an unchanged efficacy profile [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Even though a recent study by Juzot et al (in preparation) did not report any predictive factors of response to vismodegib, similar data regarding radiotherapy have been reported in a small series of patients. 8 Nevertheless, as our data are retrospective, we must analyse these results with caution and a causal relationship cannot be asserted. The low number of events did not allow us to consider potential confounders (i.e.…”
Section: Characterization Of Patients With Advanced Basal Cell Carcin...mentioning
confidence: 93%